2003
DOI: 10.1063/1.1609400
|View full text |Cite
|
Sign up to set email alerts
|

H-substituted anionic carbon clusters CnH− (n⩽10): Density functional studies and experimental observations

Abstract: We have studied the interaction of hydrogen with small neutral and anionic carbon clusters using density functional calculations. The geometry, stability, and electronic structure of these clusters show an odd-even alternation originating in the bonding nature of the carbon atoms. Our mass spectrometric measurements of the abundance of C n H Ϫ (nр10) cluster anions produced by gas-feed Cs sputtering from different crystallographic forms of carbon display similar odd-even alternation with the even-n clusters be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 51 publications
8
28
0
Order By: Relevance
“…Their results showed that the geometry of the C 4 N − and C 6 N − ions at the local minimum were not linear . The experimental observation of a higher intensity of the C x H − ion when x was an even number was also in agreement with the density functional theory calculations by Pan et al This kind of discrete pattern in the negative ion spectra indicates that the formation of an anion is dependent on its stability. The same discrete pattern observed in SIMS experiment seems to suggest that ion stability again is an important factor in anion formation.…”
Section: Negative Ion Spectra Of P2vp and P4vpsupporting
confidence: 61%
“…Their results showed that the geometry of the C 4 N − and C 6 N − ions at the local minimum were not linear . The experimental observation of a higher intensity of the C x H − ion when x was an even number was also in agreement with the density functional theory calculations by Pan et al This kind of discrete pattern in the negative ion spectra indicates that the formation of an anion is dependent on its stability. The same discrete pattern observed in SIMS experiment seems to suggest that ion stability again is an important factor in anion formation.…”
Section: Negative Ion Spectra Of P2vp and P4vpsupporting
confidence: 61%
“…One possible explanation could be that ions with a small number of carbon atoms can form both through the direct breaking up of the carbon structure of the HOPG and also through the breakup of larger ions . C x − ions with an even number of carbons are more stable than those with an odd number, and the stability of the C x − ions oscillates between even and odd values of x . The normalized intensities of the C x − ions in the sputtered HOPG after 800°C annealing were again similar to those in the fresh HOPG.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the rotational spectra of the deuterated species were obtained at the expected isotopic shifts (7.1% and 3.3%, respectively) to better than 0.05%. The absence of fine and hyperfine structure in the high-resolution FTM measurements (line width 10-20 kHz) and the closely harmonic sequence of the lines strongly indicate closed-shell linear molecules with ground states, as predicted (Pan et al 2003; Pino et al 2002).…”
Section: ϫ7 ϫ9mentioning
confidence: 90%
“…The ground states of both C 4 H Ϫ and C 8 H Ϫ have been predicted from ab initio calculations and photodetachment experiments to be (Pan et al 2003;Pino et al 2002). The 1 ϩ S expected rotational spectra therefore are those of simple linear molecules, devoid of the fine and hyperfine structure that is present in the neutral radicals, which possess or ground 2 ϩ 2 S P states.…”
Section: ϫ7 ϫ9mentioning
confidence: 96%